A Quantitative Analysis of the Little Red Riding Hood Types and Story Element-Function-Plot Relations - Park, Jungsik; Han, Ho (Korean Journal of English Language and Linguistics, 2022)
Tale types of “Little Red Riding Hood” have survived through oral transmission in various areas including Europe, Africa, and Asia and can even be traced back to 10th century in a written form. This research presents quantitative analyses on the folkloric landscape of tales of, or related to, what is best known as Little Red Riding Hood through the Aarne-Thompson-Uther (ATU) index, of which we analyzed ATU 333, ATU 123, and other unspecified types, based on logistic regression and decision tree. The quantitative analyses of the Little Red Riding Hood tale types indicate that ATU 123 alone has the specific story segments that are important to the formation of the tale type and that though diversified in story segments and other details, the three types shared the distinct plot sequence as an important feature. In addition, eight event descriptors and six character and setting descriptors are found to be meaningful factors in the formation of ATU 123. It can be further argued that the plot as an abstraction played a major role in the formation of the tales we have now. Also demonstrated in this paper is that researchers can yield substantial insights into the quantitative results while cross-checking them with qualitative analyses.
Keywords: feature importance; Little Red Riding Hood; logistic regression; motif; plot; story element